2013
DOI: 10.1371/journal.pone.0070316
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Honeydew-Consuming Fungal Communities Associated with Scale Insects

Abstract: Sooty mould fungi are ubiquitous, abundant consumers of insect-honeydew that have been little-studied. They form a complex of unrelated fungi that coexist and compete for honeydew, which is a chemically complex resource. In this study, we used scanning electron microscopy in combination with T-RFLP community profiling and ITS-based tag-pyrosequencing to extensively describe the sooty mould community associated with the honeydews of two ecologically important New Zealand coelostomidiid scale insects, Coelostomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
0
28
1
3
Order By: Relevance
“…Although a variety of insects and other animals exploit honeydew for its sugar resources (Beggs and Wardle ), and a recent investigation revealed that many taxonomically diverse fungi compete for honeydew (Dhami et al. ), no Saccharomyces species were found associated with aphid honeydew from Black Beach trees in New Zealand (Serjeant et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of insects and other animals exploit honeydew for its sugar resources (Beggs and Wardle ), and a recent investigation revealed that many taxonomically diverse fungi compete for honeydew (Dhami et al. ), no Saccharomyces species were found associated with aphid honeydew from Black Beach trees in New Zealand (Serjeant et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of associations and infection types has been discovered, ranging from parasitic through commensal and even beneficial (Suh et al 2005, Vega et al 2012, Douglas 2015. High-throughput sequencing is rapidly gaining in popularity as a means of studying fungus-insect interactions, and published studies have uncovered surprising diversity even within single insect individuals (e.g., Dhami et al 2013). This is in line with the results from other environmental fungal sequencing efforts, where tens to hundreds of previously unknown (or at least not sequenced) species are usually found in each new study undertaken (Nilsson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, feeding on the honeydew that drips onto the bark is black sooty mold, which covers the beech trees and also provides food for many native arthropods (Morales et al 1988). A recent study by Dhami et al (2013) showed that the sooty mold community found on black beech is much more diverse than previously thought and is comprised of more than 40 genera belonging to the Ascomycota and Basidiomycota fungal divisions.…”
Section: Introductionmentioning
confidence: 99%